The Effect of COVID-19-related Occupational Stress and Burnout in Referral Hospital Nurses - Arif, Yulastri; Fadhani, Masyithah (UI Scholars Hub, 2023)
Nurses' continuous contribution to patient health makes them prone to occupational stress, which has been exacerbated during the COVID-19 pandemic. Occupational stress that lasts for a long time and is not resolved may cause burnout. Burnout experienced by nurses can impact patients, hospital services, and themselves. This study aimed to determine the effect of occupational stress on the incidence of nurse burnout during the COVID-19 pandemic. It used a quantitative approach with a cross-sectional design. The study sample was 235 nurses in six COVID-19 referral hospitals in West Sumatra from a proportional random sampling technique. Data were collected using a digital questionnaire distributed via a Google Forms link from February to April 2022. The results showed that the stress level of nurses was most commonly moderate (68.1%), and the burnout level was most commonly low (82.1%), with a significant effect of occupational stress on burnout. This study reveals the effect of occupational stress on the burnout of nurses treating COVID-19 patients.